Expert opinion on the use of cladribine tablets in clinical practice. (June 2020) - Sørensen, Per Soelberg; Centonze, Diego; Giovannoni, Gavin; Montalban, Xavier; Selchen, Daniel; Vermersch, Patrick; Wiendl, Heinz; Yamout, Bassem; Salloukh, Hashem; Rieckmann, Peter
Background: Gaps in current product labels and a lack of detailed clinical guidelines leaves clinicians' questions on the practical management of patients receiving cladribine tablets for the treatment of relapsing multiple sclerosis (MS) unanswered. We describe a consensus-based programme led by international MS experts with the aim of providing recommendations to support the use of cladribine tablets in clinical practice. Methods: A steering committee (SC) of nine international MS experts led the programme and developed 11 clinical questions concerning the practical use of cladribine tablets. Statements to address each question were drafted using available evidence, expert experiences and perspectives from the SC and an extended faculty of 33 MS experts, representing 19 countries. Consensus on recommendations was achieved when ⩾75% of respondents expressed an agreement score of 7–9, on a 9-point scale. Results: Consensus was achieved on 46 out of 47 recommendations. Expert-agreed practical recommendations are provided on topics including: the definition of highly active disease; patterns of treatment response and suboptimal response with cladribine tablets; management of pregnancy planning and malignancy risk, infection risk and immune function, and switching to and from cladribine tablets. Conclusion: These expert recommendations provide up-to-date relevant guidance on the use of cladribine tablets in clinical practice.